Novel components of Tityus serrulatus venom: A transcriptomic approach. (15th January 2021) - Kalapothakis, Yan; Miranda, Kelton; Pereira, Adriana Heloísa; Witt, Amanda S.A.; Marani, Camila; Martins, Ana Paula; Leal, Hortênsia Gomes; Campos-Júnior, Edimar; Pimenta, Adriano M.C.; Borges, Adolfo; Chávez-Olórtegui, Carlos; Kalapothakis, Evanguedes
Abstract: Several research groups have studied the components produced by the venom gland of the scorpion Tityus serrulatus, which has one of the most lethal venoms in the world. Various methodologies have been employed to clarify the complex mechanisms of action of these components, especially neurotoxins and enzymes. Transcriptomes and proteomes have provided important information for pharmacological, biochemical, and immunological research. Next-generation sequencing (NGS) has allowed the description of new transcripts and completion of partial sequence descriptions for peptides, especially those with low expression levels. In the present work, after NGS sequencing, we searched for new putative venom components. We present a total of nine new transcripts with neurotoxic potential (Ts33–41) and describe the sequences of one hyaluronidase (TsHyal_4); three enzymes involved in amidation (peptidyl-glycine alpha-amidating monooxygenase A, peptidyl-alpha-hydroxyglycine alpha-amidating lyase, and peptidylglycine alpha-hydroxylating monooxygenase), which increases the lethal potential of neurotoxins; and also the enzyme Ts_Chitinase1, which may be involved in the venom's digestive action. In addition, we determined the level of transcription of five groups: toxins, metalloproteases, hyaluronidases, chitinases and amidation enzymes, including new components found in this study. Toxins are the predominant group with an expression level of 91.945%, followed by metalloproteases with only 7.790% and other groups representing 0.265%. Highlights: Nine new toxins (Ts33–41) of Tityus serrulatus, with probable sodium channel activity, are described. The complete amino acid sequences of five T. serrulatus toxins (Ts7, Ts13, Ts15, Ts27, and Ts30) are presented. One new hyaluronidase, three new amidation-related enzymes (PHM, PAM, and PAL), and the enzyme Ts_Chitinase1 are described. Sixty-seven contigs identified: 35 toxins, 25 metalloproteases, 3 hyaluronidases, 1 chitinases, and 3 amidation enzymes. Transcription levels of the 67 identified contigs reinforce the predominance of toxins (91.945%).